Is Labor Market Mismatch a Big Deal in Japan? - Shibata, Ippei (IMF Working Papers; Working Paper ;, 2013)
Despite its low unemployment rate, the recent shift in the Japanese Beveridge curve indicates increased labor mismatch. This paper quantifies the age, employment-type (full or part-time), and occupational mismatch in the Japanese labor market following Sahin and others (2013). Between April 2000 and April 2013, the age mismatch has steadily declined while the occupational and employmenttype mismatch has shown a countercyclical pattern, showing a sharp increase during the global financial crisis. Occupational mismatch accounted for approximtely 20-40 percent of the recent rise in the unemployment rate in Japan. The magnitude was comparable to that of the U.K. and the U.S.